Analysis of Business Capital, Labor, Number of Consumers and Production on SMEs Income in Medan Petisah District - Muhamad Toyib Daulay; Annisa Sanny (Proceeding of The International Conference on Business and Economics, 2023)
The effect of the independent variable on the dependent variable, which is entitled " Analysis of Business Capital, Labor, Number of Consumers and Production on UKM Income in Medan Petisah District". In this study, researchers used primary data using a population of 176 and a sample of 122 SMEs in the restaurant sector. Based on the results of data processing using the SPSS version 16.0 application, capital has a significant direct effect on income. Labor has a significant direct effect on income. Consumers have a significant direct effect on income. And based on path analysis research, the results of data processing show that the value of capital has a positive effect on income through production as an intervening variable. Labor has a positive effect on income through production as an intervening variable. Consumers have a positive effect on income through production as an intervening variable.